现在各种 AI大模型层出不穷,每家都说自己如何强,我们就拿一道简单的初一数学题喂给当前主流的 AI 大模型看看结果。
(X 1)/3=1-(x-1)/2, what is X?
下面是结果:
1. 羊驼Code-Llama-34b
We are given the equation:
(X 1)/3 = 1 - (X-1)/2
First, let's simplify the left-hand side of the equation:
X 1 = 3 - 2(X-1)
Expanding the right-hand side:
X 1 = 3 - 2X 2
Comparing both sides:
X 1 = 3 - 2X 2
Subtracting 1 from both sides:
X = 2
So, X equals 2.
2. Cloude
Okay, let's solve this step-by-step:
(X 1)/3 = 1-(x-1)/2
Multiply both sides by 3:
X 1 = 3 - (x-1)
Combine like terms:
X 1 = 3 - x 1
Add x-1 to both sides:
X 1 x - 1 = 3
Combine like terms:
X x = 4
Add -x to both sides:
X = 4 - x
Add x to both sides:
X x = 4
We know from above that X x = 2x
Therefore, 2x = 4
Divide both sides by 2:
x = 2
Therefore, the value of X is 2.
So the answer is: X = 2
3. Poe Assistant
To solve the equation (x 1)/3 = 1 - (x - 1)/2 for X, we can start by simplifying the equation:
Multiply both sides of the equation by 6 to eliminate the denominators:
2(x 1) = 6 - 3(x - 1)
Next, distribute the multiplication:
2x 2 = 6 - 3x 3
Combine like terms:
2x 2 = 9 - 3x
Now, we want to isolate the variable X on one side of the equation. Let's add 3x to both sides:
2x 3x 2 = 9
Combine like terms again:
5x 2 = 9
Subtract 2 from both sides:
5x = 7
Finally, divide both sides by 5:
x = 7/5
Therefore, the value of X is 7/5 or 1.4.
4. ChatGPT 3.5
To solve the given equation:
(X 1)/3 = 1 - (X - 1)/2
We can start by simplifying the equation by multiplying both sides by the least common denominator (LCD), which in this case is 6:
6 * [(X 1)/3] = 6 * [1 - (X - 1)/2]
2(X 1) = 6 - 3(X - 1)
2X 2 = 6 - 3X 3
2X 2 = 9 - 3X
Next, we can group the X terms on one side and the constants on the other side:
2X 3X = 9 - 2
5X = 7
Finally, we isolate X by dividing both sides by 5:
X = 7/5
Therefore, the solution to the equation is X = 7/5 or 1.4.
5. 百度文心一言
我们有一个数学方程:(X 1)/3 = 1-(x-1)/2, 我们的任务是找出 X 的值。
为了解决这个问题,我们首先需要理解和分析这个方程。
这个方程告诉我们 X 和 1 的关系,以及 (x-1) 和 2 的关系。
我们的目标是解出 X 的值。
首先,我们可以简化方程的左边:(X 1)/3 = X/3 1/3
然后,我们可以简化方程的右边:1-(x-1)/2 = 2/2 - (x-1)/2 = 1 - x/2 1/2 = 3/2 - x/2
现在我们可以把两边相等,即:X/3 1/3 = 3/2 - x/2
我们可以把这两个方程合并为一个新的方程,并解出 X 的值。
计算结果为:X = 1.4
所以,X 的值为:1.4
6. 通义千问
To solve the equation (X 1) / 3 = 1 - (X - 1) / 2, we need to multiply both sides of the equation by the least common multiple of 3 and 2, which is 6.
Multiplying both sides by 6 gives:
2(X 1) = 6 - 3(X - 1)
Expanding this expression gives:
2X 2 = 6 - 3X 3
Bringing all terms containing X to one side, we get:
5X = 7
Finally, dividing both sides by 5 gives:
X = 7/5
Therefore, the solution to the equation (X 1) / 3 = 1 - (X - 1) / 2 is X = 7/5.
所以你觉得哪家 AI 更强?